Macrophage-Derived Tumor Necrosis Factor α, an Early Developmental Signal for Motoneuron Death - Sedel, Frédéric (J Neurosci, 2004)
Mechanisms inducing neuronal death at defined times during embryogenesis remain enigmatic. We show in explants that a developmental switch occurs between embryonic day 12 (E12) and E13 in rats that is 72-48 hr before programmed cell death. Half the motoneurons isolated from peripheral tissues at E12 escape programmed cell death, whereas 90% of motoneurons isolated at E13 enter a death program. The surrounding somite commits E12 motoneurons to death. This effect requires macrophage cells, is mimicked by tumor necrosis factor α (TNFα), and is inhibited by anti-TNFα antibodies. In vivo, TNFα is detected within somite macrophages, and TNF receptor 1 (TNFR1) is detected within motoneurons precisely between E12 and E13. Although motoneuron cell death occurs normally in TNFα(-/-) mice, this process is significantly reduced in explants from TNFα(-/-) and TNFR1 (-/-) mice. Thus, embryonic motoneurons acquire the competence to die, before the onset of programmed cell death, from extrinsic signals such as macrophage-derived TNFα